COMPARISON OF RETROGRADE INTRARENAL SURGERY OUTCOME VERSUS PERCUTANEOUS NEPHROLITHOTOMY IN RENAL STONES >2 CM IN DIAMETER IN LOWER CALYCES AT A TERTIARY CARE HOSPITAL - IMRAN, M; RASOOL, M; KHAN , IA; BOOBAK, A; IMRAN , SMA; SAFDAR, S (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to compare the outcome of Retrograde Intrarenal Surgery and Percutaneous Nephrolithotomy in treating renal stones larger than 2 cm in diameter in lower calyces at a tertiary care hospital. A randomized control trial was conducted at the Department of Urology, Bahawal Victoria Hospital, Bahawalpur, for 8 months from 01-06-2021 to 01-02-2022 using a non-probability purposive sampling technique. Seventy patients met the inclusion and exclusion criteria and were enrolled in the study. The patients were randomly divided into two groups using a lottery method. Group A underwent PCNL, while Group B underwent RIRS. During the procedure, the operative time was noted from the time of intubation to the time of extubation. After the procedure, the duration of hospital stay was noted, and the patients were followed up in the OPD for 12 weeks. After 12 weeks, an abdominal ultrasound was conducted to evaluate if there were any residual stones. If there were no residual stones, the patients were labeled stone-free. Seventy patients participated in the study, with a mean age of 45.51±13.68 years, ranging from 20 to 69 years. The mean age of patients in the RIRS group was 47.63 ± 13.51 years, while in the PCNL group, it was 43.40 ± 13.71 years, with a non-significant p-value of 0.198. The gender distribution among the patients revealed that 30 (42.86%) were male and 40 (57.14%) were female, with an equal distribution of males (15, 42.9%) in both the RIRS and PCNL groups. However, there were substantial differences in the duration of surgery, with the RIRS group having a mean operative time of 107.57 ± 6.99 minutes and the PCNL group having a significantly shorter mean operative time of 75.86 ± 7.19 minutes (p-value < 0.001). Moreover, the RIRS group had a shorter mean hospital stay, with 4.77 ± 1.03 days compared to 5.46 ± 1.09 days in the PCNL group (p-value = 0.009). Post-procedure, 63 (90%) patients achieved stone-free status, with 29 (82.9%) patients in the RIRS group and 34 (97.1%) in the PCNL group, with a non-significant p-value of 0.106. This study concluded that RIRS is a safe procedure and a good alternative to PCNL in treating renal stones larger than 2 cm in diameter in lower calyces to achieve stone-free status and length of hospital stay.